Shifting paradigms and arising concerns in severe hemophilia A treatment - Chandran, Rubhan; Tohit, Eusni R. Mohd.; Stanslas, Johnson; Salim, Norazlinaliza; Mahmood, Tuan M.T.; Rajagopal, Mogana (Thieme Gruppe, 2024)
The management of hemophilia A has undergone a remarkable revolution, in line with technological advancement. In the recent past, the primary concern associated with Factor VIII (FVIII) concentrates was the risk of infections, which is now almost resolved by advanced blood screening and viral inactivation methods. Improving patients' compliance with prophylaxis has become a key focus, as it can lead to improved health outcomes and reduced health care costs in the long term. Recent bioengineering research is directed toward prolonging the recombinant FVIII (rFVIII) coagulant activity and synthesising higher FVIII yields. As an outcome, B-domain deleted, polyethylene glycolated, single-chain, Fc-fused rFVIII, and rFVIIIFc-von Willebrand Factor-XTEN are available for patients. Moreover, emicizumab, a bispecific antibody, is commercially available, whereas fitusiran and tissue factor pathway inhibitor are in clinical trial stages as alternative strategies for patients with inhibitors. With these advancements, noninfectious complications, such as inhibitor development, allergic reactions, and thrombosis, are emerging concerns requiring careful management. In addition, the recent approval of gene therapy is a major milestone toward a permanent cure for hemophilia A. The vast array of treatment options at our disposal today empowers patients and providers alike, to tailor therapeutic regimens to the unique needs of each individual. Despite significant progress in modern treatment options, these highly effective therapies are markedly more expensive than conventional replacement therapy, limiting their access for patients in developing countries.